Evaluation of Effects of Dextrometorphan and Midazolam onMorphin-Induced Tolerance and Dependence in Mice: Morphine tolerance and dependence - Bohlul Habibi Asl,; Kambiz Hassanzadeh, (Iranian Journal of Pharmaceutical Sciences, 2008)
Long-term exposure to opiates induces physical dependence and tolerance. The main goal of this study was to evaluate the effects of dextromethorphan and midazolam and their combination on morphine tolerance and dependence in mice.Different groups of mice were rendered randomly and received morphine (50mg/kg, sc), morphine (50 mg/kg, sc) + dextromethorphan (25,50 or 75 mg/kg, ip),morphine (50 mg/kg, sc) + midazolam (0.5, 1, 2 mg/kg, ip), morphine (50 mg/kg,sc) + dextromethorphan (25 mg/kg, ip) + midazolam (0.5 mg/kg, ip) once a day for four days. Tolerance was assessed by administration of morphine (9 mg/kg, ip) onthe fifth day. Withdrawal symptoms (markers for dependence) was assessed byadministration of naloxone (4 mg/kg, ip) two hours after co-administration ofmorphine with either dextromethorphan or midazolam or their combination groups. Results showed that pretreatment with dextromethorphan or midazolam decreased the degree of tolerance and withdrawal symptoms significantly.Additionally, co-administration of dextromethorphan and midazolam before morphine administration decreased the tolerance and dependence but it was not significant.From these results, it may be concluded that dextromethorphan and midazolam alone or in combination could prevent the development of tolerance and dependence tothe analgesic effects of morphine. These effects can be related to the N-methyl-D-aspartate (NMDA) receptor antagonist behavior of dextromethorphan and GABA-receptor agonist behavior of midazolam.